Challenges associated with metal chelation therapy in alzheimer's disease - Hegde, Muralidhar L.; Bharathi, P.; Suram, Anitha; Venugopal, Chitra; Jagannathan, Ramya; Poddar, Pankaj; Srinivas, Pullabhatla; Sambamurti, Kumar; Rao, Kosagisharaf Jagannatha; Scancar, Janez; Messori, Luigi; Zecca, Luigi; et al. (Journal of Alzheimers Disease, 2009)
A close association between brain metal dishomeostasis and the onset and/or progression of Alzheimer's disease ( AD) has been clearly established in a number of studies, although the underlying biochemical mechanisms remain obscure. This observation renders chelation therapy an attractive pharmacological option for the treatment of this disease. However, a number of requirements must be fulfilled in order to adapt chelation therapy to AD so that the term ``metal targeted strategies'' seems now more appropriate. Indeed, brain metal redistribution rather than brain metal scavenging and removal is the major goal of this type of intervention. The most recent developments in metal targeted strategies for AD will be discussed using, as useful examples, clioquinol, curcumin, and epigallocatechin, and the future perspectives will also be outlined.
Keywords: Alzheimer's disease; clioquinol; cuprizone; metal dishomeostasis; metal ions; nanomedicine; Parkinson's disease; polyphenols